Spatial mapping of winter wheat using C-band SAR (Sentinel-1A) data and yield prediction in Gorakhpur district, Uttar Pradesh (India). Issue 1 (2nd January 2023) - Parida, Bikash Ranjan; Singh, Sheelu
ABSTRACT: Spatial depiction of wheat and predicting yields are crucial for national food security measures. This study has employed multi-temporal synthetic aperture radar (SAR) data for spatial mapping of winter wheat and estimating its acreage in the Gorakhpur district. Results showed that the estimated acreage of winter wheat based on SAR data was 189, 740 hectares. Accordingly, the yield and production were predicted as 3.9 tonnes/ha and 740, 000 tonnes, respectively, using a polynomial model. VH polarisation was effective in acreage mapping compared to VV. Thereby, the developed framework could support policymakers by giving advanced estimates of area and yield.